Pengaruh Pelatihan terhadap Produktivitas Kerja Karyawan PT Tri Keeson Utama Garut - Putra, Andre Harpadiansyah; Yusuf, Ramayani (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
Every company certainly wants to achieve success. To achieve this, companies need a strategy to face increasingly fierce competition. One of the things that companies must pay attention to in achieving success is training. This study aims to examine how much influence the training has on the work productivity of employees at PT. Tri Keeson main Garut. This research uses quantitative methods, the object of this research is all employees at PT. Tri Keeson Utama Garut.. The sample in this study was 70 employees using the slovin method by distributing questionnaires. The data in this study were analyzed using simple linear regression. The results obtained in this study indicate that there is a positive and significant effect of training on employee productivity at PT. Tri Keeson Utama Garut, it can be assumed that the quality of the training provided to employees is very good to assist companies in creating good work productivity.